SIGNIFICANCE OF MOLECULAR BIOMARKERS IN THE DIAGNOSIS OF NEUROMYELITIS OPTICA SPECTRUM DISORDER - Andabaka, Marko; Novaković, Ivana; Drulovic, Jelena (Medicinski podmladak, 2024)
Discovery of antibodies to aquaporin-4 channels as a laboratory or molecular biomarker for neuromyelitis optica spectrum disorder contributed to a better understanding of the etiopathogenesis with a clear separation of the clinical, neuroradiological and laboratory characteristics of this disease, which resulted in the definition of criteria for establishing the diagnosis of neuromyelitis optica spectrum disorder and a clear distinction in relation to multiple sclerosis. Clinical presentation of the inflammatory diseases of the central nervous system may be highly variable, with numerous, often overlapping symptoms and signs. Therefore, in the differential diagnostic, in addition to the clinical presentation, it is necessary to consider paraclinical characteristics, such as laboratory findings of the blood and cerebrospinal fluid and the neuroradiological examination findings. Since aquaporin-4 is a clearly defined crucial diagnostic biomarker in the neuromyelitis optica spectrum disorder, different methodological approaches were developed to test antibodies to aquaporin-4 taking into account the specificity and sensitivity of the tests themselves. One of the first tests that was routinely applied in clinical practice for the detection of antibodies to aquaporin-4 were tests in the form of an immunoenzymatic assay that showed great variability in the degree of specificity and sensitivity. The second group of tests for the detection of antibodies to aquaporin-4 applied the technique of indirect immunofluorescence on a substrate of animal origin, which achieved a higher degree of sensitivity and specificity with certain disadvantages such as the impossibility of precise quantification as well as difficulties in the interpretation of the results. Special methodological principles of immunoprecipitation such as fluorescent and radioimmunoprecipitation did not achieve a satisfactory level of sensitivity in the detection of antibodies to aquaporin-4. The highest level of sensitivity with absolute specificity has been achieved via developing a cell assay methodology based on the application of human aquaporin-4 transfected cells fixed on a biochip with a negative control when antibodies to aquaporin-4 from serum are detected by indirect immunofluorescence methodology or special cellular assays when these antibodies are quantified by flow cytometry method. The possibility to use this cell assaymethodology is extremely important in order to establish the correct diagnosis of seropositive neuromyelitis optica spectrum disorder.